The impact of Citizens United: How the removal of independent expenditure bans shaped U.S. gubernatorial elections - Patrick Balles (University of Basel, Center of Business and Economics (WWZ), 2024)
This paper examines the U.S. Supreme Court's 2010 Citizens United decision, which lifted bans on independent expenditures by corporations and unions. Using a difference-in-differences design, the study compares states with and without pre-existing bans, focusing on gubernatorial elections. The results show an 11 percentage point increase in the share of Republican TV ad airings following the removal of independent expenditure bans. This increase is especially pronounced (16 percentage points) in states where only corporate bans were lifted, with total TV ad airtime rising by over 29 hours on average. Negative campaigning also intensified, with a 5.5 percentage point rise in the share of attack ads. Survey and election data show a significant demobilization effect, particularly in states where only corporate bans were removed (3.5-5 percentage point decrease in county-level turnout). Finally, Republican gubernatorial candidates experienced a 7-11 percentage point boost in vote shares following the removal of independent spending bans.
Keywords: D72; K16; L82; 330; campaign finance; Citizens United v. FEC; independent expenditures; voter turnout; television markets; special interest groups; corporate money in politics